Penanaman Karakter Anak Usia 5-6 Tahun di TK Pertiwi Pakualaman (Studi Kasus pada Taman Kanak-Kanak Pertiwi Pakualaman Yogyakarta, tahun 2018) - Utami, Novianti Retno; Iman Utama, Windi Wulandari (?ALI?A, 2019)
This research aims to describe a process attachment of character early childhood education in kindergartens PERTIWI PAKUALAMAN YOGYAKARTA. Subject at this research are 13 of early childhood for 5-6 years old and 2 teachers. Data were collected through a observation, interview, and documentation. The data were analyzed use Miles and Huberman Models are reduction, data serving, and verification. The research result are as follows: (1) java’s culturu “pitutur jawa” that was attached as a method for shaping behavior in children. (2) java’s culture can shaping positive behavior. (3) positive behavior that appear from the children are patient, fortunately, brave, seriously to take something, responsible, low profile.